Psychological Peculiarities of Emotional Burning out of Ambulance Doctors - Pasterik, T. V. (Psychological Prospects Journal, 2011)
The psychological peculiarities of emotional burning out of ambulance doctors are highlighted in the article. The differences of emotional burning out indices according to seniority are revealed. The results of penetrating training program show its efficiency.
Keywords: emotional burning out ambulance doctors seniority training program